The Anticonvulsant and Antioxidant Effect of Rosa Moschata (J) Fruit Extract in Pentylenetetrazole induced Epileptic Mouse Model - Irshad, Zainab; Nawaz, Samia; Ullah, Shakir; Ali, Niaz; Khan, Imran; Nabi, Muhammad (International Journal of Pathology, 2024)
Background: Rosa moschata (J) (RM (J)) is widely used as a traditional medicine in different ailments including central nervous system diseases, hepatic and gastrointestinal disease. The current study focused on the anticonvulsant effects and memory improvement property of RM (J) fruit extract by the modulation of oxidative stress markers and GABAA receptor in pentylenetetrazole (PTZ) induced mice epileptic model. Methods: The epileptic mice model was developed using pentylenetetrazole (35 mg/kg). The extract were used at doses of 50 mg/kg, 100 mg/kg and 150 mg/kg. The seizure was evaluated according to the Racine Scale. Cognitive functions were evaluated using the Y Maze and Morris Water Maze behavioral tests. The antioxidant effect of RM (J) extract was measured by assessing the level of lipid peroxidation (LPO), superoxide dismutase (SOD), glutathione (GSH), and catalase (CAT). Additionally, the effect of RM (J) extract on the expression of GABAA receptors was evaluated using the qPCR. Results: RM (J) fruit extract exhibited a significant (P<0.5) dose-dependent improvement in memory compared to the mice treated with PTZ. Furthermore, the RM (J) extract significantly increased the levels of GSH and CAT and reduced LPO level compared to the PTZ group. The onset time of seizure was prolong while duration of seizure was significantly short in RM (J) extract treated group compared to PTZ group. Interestingly, there was a significant increase in the expression of GABAA receptors in the groups treated with the RM (J) extract, compared to the PTZ group. Conclusions: RM (J) extracts showed anticonvulsant effect and memory improvement potential due to the reduction of oxidative stress markers and enhanced in the expression of GABAA receptors.